2021
DOI: 10.1038/s41598-021-97878-0
|View full text |Cite
|
Sign up to set email alerts
|

Gestalts at threshold could reveal Gestalts as predictions

Abstract: We review and revisit the predictive processing inspired “Gestalts as predictions” hypothesis. The study of Gestalt phenomena at and below threshold can help clarify the role of higher-order object selective areas and feedback connections in mid-level vision. In two psychophysical experiments assessing manipulations of contrast and configurality we showed that: (1) Gestalt phenomena are robust against saliency manipulations across the psychometric function even below threshold (with the accuracy gains and high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 88 publications
(102 reference statements)
0
2
0
Order By: Relevance
“…The results of both Experiments 3 and 4 extend previous research into the perception of dot arrays with a very small number of dots (Pomerantz and Portillo, 2011;Hawkins et al, 2016;Costa and Wagemans, 2021). In those experiments, the configural superiority effect (CSE) paradigm was used to show that an odd-one-out task could be facilitated by the addition of identical elements provided those elements resulted in different emergent features like orientation or proximity in the target display than the distractors.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The results of both Experiments 3 and 4 extend previous research into the perception of dot arrays with a very small number of dots (Pomerantz and Portillo, 2011;Hawkins et al, 2016;Costa and Wagemans, 2021). In those experiments, the configural superiority effect (CSE) paradigm was used to show that an odd-one-out task could be facilitated by the addition of identical elements provided those elements resulted in different emergent features like orientation or proximity in the target display than the distractors.…”
Section: Discussionsupporting
confidence: 69%
“…They found that observers are highly sensitive to orientation and proximity relations between pairs of dots (see also Hawkins et al, 2016). These relations were shown to influence performance in an odd-one-out task even as differences between the target and distractor approached the minimum threshold for detection (Costa and Wagemans, 2021). Higher-order relations among dots resulted…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence suggests that the visual system treats social scenes in a configurational manner, prioritizing the dyad's processing over the processing of separate individuals [9][10][11][12][13][14]. Moreover, the observation that Gestalt phenomena are robust to visibility manipulations [17] further supports the idea that perceptual grouping may occur even when part of the stimuli is masked by noise. Hence, an alternative interpretation for previous social prediction findings [4][5][6][7][8] could be delineated as follows: When the point-light displays were spatiotemporally aligned in a meaningful way, their configural patterns tapped into the visual system bias to efficiently bind social information leading to visual detection enhancement.…”
Section: Introductionmentioning
confidence: 92%
“…It is widely known that our visual system prioritizes the processing of social interactions as a whole, over the processing of individual actions [84][85][86]. We also know that perceptual grouping may occur even when part of the stimuli is masked [87]. Likewise, spatiotemporal simulation of a 'missing part' might be generated to be compared in real-time with the upcoming input during social interactions [11].…”
Section: The Encoding Of Incomplete Joint Actionsmentioning
confidence: 99%